Promoting Your Language on Social Media - Firth-Hagen, Jacey; Fanene, William; Okon, Ben; Elliot, Robert; Mufwene, Salikoko (Zenodo, 2021)
Note: This talk has not gone through a process of peer review, and findings should therefore be treated as preliminary and subject to change. SOAS Linguistics Webinar Tuesday 29 September 2020 Jacey Firth-Hagenpromotes the Gwich’inlanguage (Athabascan)using #speakGwichintomeacross several platformssuch as Instragram(@speakGwichintome),Twitter (@SpeakGwichin) andFacebook (Gwich’inLanguage Revival Campaign). William Fanenepromotes the Samoanlanguage (Polynesian) onInstagram (@amuuso) andthrough the website:matousamoa.com Ben Okonpromotes the Efik language(Cross River) on Twitter(@BenOkon11) andFacebook. Robert Elliotis associate director of theNorthwest IndianLanguage Institute (NILI)at the University ofOregon where he partnerswith numerous tribes inthe Pacific Northwest andbeyond on indigenouslanguage revitalization. Salikoko Mufwene is the Frank J. McLoraineDistinguished ServiceProfessor of Linguisticsand the College at theUniversity of Chicago.His research is inevolutionary linguistics,which he approachesfrom an ecologicalperspective. Abstract: Most languages in the world are being spoken by fewer and fewer people, and the prevalenceof English and other major world languages on the internet may be further boosting this trend.However, the internet is also being used to promote linguistic diversity. In this panel discussion,three language activists will share what motivates them to promote their languages (Gwich’in,Samoan and Efik) on social media, and what impact they have seen through their efforts. Tworespondents, Robert Elliot and Salikoko Mufwene, will share their perspectives on how languageactivism via social media can be made as effective as possible.